Perancangan Training dengan E-Learning pada Perusahaan Manufacture - Putranto, Agus (ComTech: Computer, Mathematics and Engineering Applications, 2011)
The use of information technology has been very widely in many fields including industry. Along with that, the need for a concept and mechanism of IT-based learning becomes inevitable. The purpose of this paper is to analyze the training process and identify any related problems occurred at PT.Suzuki Indomobil Motor. The problems are about the limited training time, lack of material distribution media and consultations out of training time. E-Learning is a concept of electronic application use to support learning using the internet and computer network. This concept influences the process of conventional education transformation to digital form, both in content and system. The learning system will be replaced with a web-based training media. The method used is the Object Oriented Analysis Design, which begins with a depiction of rich pictures to the Deployment diagram. This system is expected to meet the needs of employees while joining the training process, so that they will obtain excellent learning and achieve the company objectives.